Peran OSCE dalam Mengurangi Stres dan Meningkatkan Prestasi Akademik: Kajian Mahasiswa Ilmu Kesehatan di Indonesia - Ely Purnamasari; Sholeh Hidayat; Nurul Anriani (Jurnal Penelitian Pendidikan IPA, 2026)
The Objective Structured Clinical Examination (OSCE) is a high-stakes assessment that frequently triggers severe anxiety among medical and health sciences students, potentially hindering their academic success. While its evaluative rigor is well-documented, less attention has been paid to how structured preparation for OSCE can paradoxically mitigate psychological distress and foster better learning outcomes. This study aims to investigate the role of OSCE in reducing stress and enhancing academic performance among health sciences students in Indonesia. A quantitative approach with a descriptive correlational design was used to determine the relationship between OSCE implementation, stress levels, and students' academic achievement. The research sample consisted of health study program students at several universities selected purposively. The research instruments included a validated stress level questionnaire and academic grade data from OSCE results. The results showed a significant negative relationship between stress levels and OSCE scores, where reduced stress contributed to improved academic performance. The OSCE serves not only as a tool for evaluating clinical skills, but also as a learning mechanism for managing stress in high-pressure situations. The reduction in stress after the OSCE was more pronounced in students with high initial stress levels, highlighting the importance of psychological and academic preparation. Reducing stress levels was shown to have a significant impact on improving students’ performance during OSCEs, indicating the importance of stress management in supporting psychological well-being and academic success.